Ecoturismo em reservas particulares do patrimônio natural e seu papel na conservação dos ecossistemas brasileiros - Rudzewicz, Laura (My University, 2014)
Ecotourism represents one of the types of tourism that most interests contemporary society, since it relates the contact of human being with preserved nature while contributing to the local environment conservation. In Brazil, a significant diversity of ecotourism attractions is found within the natural protected areas, in which the Reserva Particular do Patrimônio Natural - RPPN represents the private category. The RPPNs are created by voluntary act from the private owner for the conservation of ecosystems, and it has become one of the main strategies in Brazilian ecosystems that face extreme threats. These areas follow a world-wide trend of enlarging private efforts for conserving biodiversity, where its compatible use through tourism is allowed under an appropriate planning and management. A descriptive and exploratory research was developed, under the qualitative and quantitative methods, with the objective to evaluate the importance of the RPPNs to the ecotourism and its role in the conservation of ecosystems. The analysis of the RPPNs in Brazil, compared to the state of Rio Grande do Sul, was based in the application of questionnaires, interviews and forms in 14 RPPNs that develop ecotourism around Brazil, and in seven areas in Rio Grande do Sul. The research was guided by the possibility of ecotourism as an instrument for the conservation of ecosystems in the RPPNs, and the results demonstrate a diversity of practices and trends being developed in these environments. The relation between environment and ecotourism in the scope of the RPPNs demonstrates that they are effective strategies to the conservation of Brazilian ecosystems. However, the practices of the concepts of ecotourism are still a challenge for its evolution.
O ecoturismo representa uma das modalidades de turismo de maior interesse na sociedade contemporânea, envolvendo o contato do ser humano com a natureza preservada e contribuindo à conservação do meio ambiente no local visitado. No Brasil, grande parte dos atrativos ecoturísticos encontra-se nas Unidades de Conservação (UCs), onde as Reservas Particulares do Patrimônio Natural (RPPNs) representam a categoria de caráter privado. As RPPNs são instituídas por ato voluntário do proprietário e destinadas à conservação dos ecossistemas, sendo uma das principais estratégias nos biomas brasileiros mais ameaçados.Essas unidades seguem uma tendência mundial de expansão dos esforços privados na conservação da biodiversidade, cujo uso compatível, por meio do turismo, é permitido, mediante planejamento e manejo adequados. Uma pesquisa exploratório-descritiva foi realizada, sob o enfoque quali-quantitativo, com o objetivo de avaliar a importância das RPPNs ao ecoturismo e o papel deste na conservação dos ecossistemas presentes nessas UCs. A análise do cenário das RPPNs no Brasil, comparado ao do Rio Grande do Sul, foi feita a partir da aplicação de questionários, entrevistas e formulários em 14 RPPNs do Brasil que desenvolvem ecoturismo, e sete unidades do Rio Grande do Sul. A pesquisa foi norteada pela questão da possibilidade de o ecoturismo vir a ser um instrumento para a conservação dos ecossistemas nas RPPNs, cujos resultados demonstram tendências e práticas diversas sendo desenvolvidas nesses ambientes. A partir da análise da inter-relação entre meio ambiente e ecoturismo, no âmbito das RPPNs, estas demonstram ser estratégias efetivas na conservação dos ecossistemas brasileiros; porém, ainda um desafio em evolução quanto à implementação dos preceitos do ecoturismo.
Keywords: Turismo; Turismo e meio ambiente; Ecoturismo; Unidades de Conservação; Reservas Particulares do Patrimônio Natural; Conservação; Ecossistemas brasileiros; Tourism and environment; Ecotourism; Protected Areas; Reservas Particulares do Patrimônio Natural; Conservation; Brazilian ecosystems; Preservação ambiental; Patrimônio natural